Exploring Effective Strategies for Student Engagement and Learning Outcomes in Elementary Education - Al Hussaini, Muzamil Hussain; Kousar, Shumalia; Kousar, Naseem; Batool, Uzma; Munawar, Nousheen (International Journal of Learning Reformation in Elementary Education, 2024)
In elementary education, enhancing student engagement and optimizing learning outcomes are paramount. This research investigates strategies to achieve these goals, exploring pedagogical approaches, classroom practices, and technology integration methods. A qualitative literature review analyzed peer-reviewed studies and empirical research, using the socio-ecological model to understand the factors influencing student engagement. Inquiry-based and project-based learning, differentiated instruction, and technology integration were identified as effective methods for fostering active participation and personalized learning. The study highlights the importance of supportive learning environments with positive teacher-student relationships and peer collaboration. SPSS software was used for quantitative analysis in studies providing statistical data on student engagement and learning outcomes.